Flow Diverters for Intracranial Aneurysms. (20th May 2014) - Alderazi, Yazan J.; Shastri, Darshan; Kass-Hout, Tareq; Prestigiacomo, Charles J.; Gandhi, Chirag D.
Abstract : Flow diverters (pipeline embolization device, Silk flow diverter, and Surpass flow diverter) have been developed to treat intracranial aneurysms. These endovascular devices are placed within the parent artery rather than the aneurysm sac. They take advantage of altering hemodynamics at the aneurysm/parent vessel interface, resulting in gradual thrombosis of the aneurysm occurring over time. Subsequent inflammatory response, healing, and endothelial growth shrink the aneurysm and reconstruct the parent artery lumen while preserving perforators and side branches in most cases. Flow diverters have already allowed treatment of previously untreatable wide neck and giant aneurysms. There are risks with flow diverters including in-stent thrombosis, perianeurysmal edema, distant and delayed hemorrhages, and perforator occlusions. Comparative efficacy and safety against other therapies are being studied in ongoing trials. Antiplatelet therapy is mandatory with flow diverters, which has highlighted the need for better evidence for monitoring and tailoring antiplatelet therapy. In this paper we review the devices, their uses, associated complications, evidence base, and ongoing studies.